Prescription of medicines by medical students of Karachi, Pakistan: A cross-sectional study - Irani Faria A; Waqar Sana; Syed Reema; Zafar Syed; Saleem Sarah (BMC, 2008)
Abstract Background Prescription of medicines by non-doctors is an issue with serious global implications. To our knowledge prescription of drugs by medical and non-medical students has not been studied before. We aimed to determine the practice and attitudes of drug prescription by medical students and: a) how non-medical students respond to this practice, b) How this compares with the attitudes and practices of non-medical students. Methods A cross-sectional study was conducted on a sample of 600 students randomly selected from 2 medical and 2 non-medical universities. Ethical requirements were ensured and data was collected using self administered questionnaires. The Chi square tests and logistic univariate regression analyses were performed using SPSS v 14 to identify associations and differences. Results A total of 572 forms were completed and the sample consisted of 295 medical students and 277 non-medical students with no significant difference in their demographic profile. Of the 295 medical students 163 (55.3%) had prescribed a medicine independently and most (48.5%) said that they did this 2-3 times a year. The commonest reasons for this were 'previous experience' (68.7%), 'problem too trivial' (34.4%) and 'we knew everything about the condition' (31.3%). One-third (33.6%) of the undergraduate medical students thought that it was alright to independently diagnose an illness while a vast majority (78.3%) thought that it was alright for them to prescribe medicines to others. Common prescriptions were pain-killers, antipyretics, antiallergics and antibiotics. Medical students who prescribed medicines were of lesser age (CI = 1.366-1.887) and more likely to belong to the 1st (CI = 3.588-21.731), 2nd (CI = 2.059- 10.869) or 3rd (CI = 4.331-26.374) year of medical college. One-third (33.9%) of the non-medical students reported that a medical student had prescribed medicines to them and 21.3% said that they trusted medical students and would follow their advice blindly. Many students thought it alright for medical students to diagnose and treat illnesses. A similar proportion of non-medical students (58.5%) reported prescribing medicines to others. Conclusion Prescription of medicines by non-doctors is rampant and urgent corrective measures are warranted. We have highlighted areas for future research and intervention and have given a few recommendations.